Gastric acid secretion in patients with duodenal ulcer treated for one year with anticholinergic drugs. Issue 10 (October 1969) - Kaye, Michael D.; Beck, Peter; Rhodes, John; Sweetnam, Peter M.
Abstract : Ninety patients with duodenal ulcer, divided randomly into three groups, were treated continuously for one year with either glycopyrronium, 1-hyoscyamine (as a sustained-release preparation) or inert tablets. Dosage with active tablets was so adjusted that the patient experienced definite but tolerable side-effects. Basal and maximal gastric acid secretion were measured immediately before and one week after cessation of treatment. There was no significant change in the means of these measurements in patients who received placebo or 1-hyoscyamine. In those given glycopyrronium, mean basal output was significantly increased. Mean maximal acid output in this group fell, but not significantly. Individual measurements of maximal acid output showed quite marked fluctuations in all groups. It is concluded that spontaneous changes in parietal cell mass may occur in patients with duodenal ulcer, and that prolonged anticholinergic therapy does not reduce parietal cell mass.